MEMBANGUN BUDAYA RELIGIOUS DI SEKOLAH - Kasri, Harwan (JURNAL ISLAMIKA, 2021)
Building a religious culture is not easy, for school-based educational institutions have various challenges to civilize religion, because it cannot be denied that schools are not intended for certain religious groups, but all religions have the right to continue their education in each school. In line with the above problems, this study aims to reveal how the opportunities and challenges faced by principals in building religious culture. This research method is qualitatively descriptive, research data obtained through observation, interviews and documentation studies. Data sources are principals, teachers and learners who are selected purposively. The results of the study are first, the Implementation of Religious Culture in SMP Negeri 5 Padang has been going well and programmed and there are evaluations carried out, ranging from the implementation of congregational prayers, the habituation of dhuha prayer, Muslim dress, guidance of tahfidz qur'an, kultum Friday, tahsin and tilawah Alqur'an, the implementation of Rohis, and the construction of Tahsin Alqur'an to all teacher councils. Second, challenges and obstacles in building a religious culture certainly exist, but all of them are considered by the principal as whips and become a morale booster to work. Third, while the opportunities owned by the principal to build a religious culture are among the regulations are very important, support from a solid teacher council, support from parents, support from the committee and support from alumni coupled with the availability of budgets. Fourth, different policies and strategies in realizing the program and goals to be achieved. So the Head of State Junior High School 5 Padang approached from heart-to-heart both to the Council of teachers and to all parties.